(untitled) (Journal of Politics and International Studies, 2024)
This paper is based on the argument that the dispute is between China, the Philippines, and Vietnam in the South China Sea. This study explores the stance of China, Vietnam, and the Philippines to save their national interest over this issue. The paper highlights the answers to the core interest of China in the South China Sea, the stances of Vietnam and the Philippines, and the hedging of all these states. Furthermore, research sheds light on the strategic significance of this region. To find out answers to these questions the research has employed qualitative methodology within the post-positivist paradigm. The basic lens of Strategic Hedging theory has applied during this research. The core finding of this research is that SCS is a complex dispute over the sovereignty of all these claimant states that puts potential threats and security implications for trade routes passing through these disputed waters as well as serious security threats among the claimants in the region.